Fusariosis - Nucci, Fabio; Nouér, Simone A.; Capone, Domenico; Anaissie, Elias; Nucci, Marcio (Seminars in Respiratory and Critical Care Medicine, 2015)
Fusarium species are frequent agents of onychomycosis and fungal keratitis, and occasional agents of invasive disease. The clinical spectrum of fusariosis in the lungs includes allergic disease (allergic bronchopulmonary fusariosis), hypersensitivity pneumonitis, colonization of a preexisting cavity, and pneumonia. Fusarial pneumonia occurs almost exclusively in severely immunocompromised patients, especially acute leukemia patients and recipients of allogeneic cell transplantation. In such patients, invasive fusariosis is usually disseminated, and pneumonia occurs in almost 50% of cases. The radiologic picture is similar to invasive aspergillosis, with alveolar infiltrates, nodules with or without halo sign, ground-glass infiltrates, and pleural effusions. Different from aspergillosis is the frequent occurrence of disseminated nodular and papular skin lesions and positive blood cultures. The drug of choice for the treatment of invasive fusariosis is either voriconazole or liposomal amphotericin B. The outcome is usually poor, and largely dependent on the recovery of the immune status of the host, particularly neutropenia.
Keywords: Fusarium; fusariosis; immunocompromised; pneumonia